2007
DOI: 10.1016/j.pedn.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional Performance of Preterm Children at Age 4

Abstract: Functional performance, a child's ability to perform the tasks of daily living and to fulfill expected social roles, is now recommended in follow-up of preterm children. This study examined neonatal, preschool health, and motor effects on functional performance at age 4. The sample of 155 infants, classified by perinatal morbidity and birth weight, was assessed during a home visit. Neonatal illness, socioeconomic status, preschool health, and motor predictors explained 44% of the variance in functional perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 33 publications
1
26
1
3
Order By: Relevance
“…Preterm children have lower scores than the normative population in assessment tests of functional performance and are independent to carry out everyday activities in three main areas of functional development: self-care, mobility and social function (19,26,27,28).…”
Section: Preterm's Functional Performancementioning
confidence: 95%
See 4 more Smart Citations
“…Preterm children have lower scores than the normative population in assessment tests of functional performance and are independent to carry out everyday activities in three main areas of functional development: self-care, mobility and social function (19,26,27,28).…”
Section: Preterm's Functional Performancementioning
confidence: 95%
“…In the study by Lemos et al (27), the sample delay percentage considering the area of functional abilities and independence of PEDI was 25.5% and 32.7%, respectively. Sullivan and Msall (19) found that preterm children scored lower on functional performance in the areas of self-care, sphincter control, transfers, mobility-locomotion, communication and social cognition. Snider et al (28) found a wide proportion of delay in functional performance in several areas: mobility, feeding, personal-social, communication, cognitive.…”
Section: Preterm's Functional Performancementioning
confidence: 99%
See 3 more Smart Citations